Perianastomotic Irrigation With Passive Drainage Dramatically Decreases POPF Rate After High-risk Pancreaticoduodenectomy. Issue 2 (15th June 2022) - Adamenko, Olga; Ferrari, Carlo; Porreca, Annamaria; Seewald, Stefan; Groth, Stefan; Gutzwiller, Jean-Pierre; Kulaksiz, Hasan; Schmidt, Jan
Abstract : Objective: To assess whether prophylactic irrigation and passive drainage of pancreatico-jejunal anastomosis could reduce leak and mortality rates after high-risk pancreaticoduodenectomies. Background: Postoperative pancreatic fistula (POPF) is a life-threatening complication following pancreaticoduodenectomy. Several risk factors have been proposed likewise potential mitigation strategies. Regarding the latter, surgical drain policy remains a "hot topic." We propose an innovative approach to mitigate POPF and POPF-related mortality following high-risk pancreaticoduodenectomies. Methods: One hundred fifty-seven patients undergoing pancreaticoduodenectomy between January 2012 and November 2021 were included in the study. Subjects with main pancreatic duct ≤ 3 mm and soft parenchyma were classified as high-risk for POPF development. Since August 2015, high-risk patients received prophylactic irrigation and drainage of the perianastomotic area. These patients were compared with risk-matched historical controls. Results: We identified 73 high-risk patients. Of these, the 47 subjects receiving prophylactic perianastomotic irrigation showed significantly lower POPF rates (12.7% vs 69.2%, P < 0.001). Multivariate regression analysis confirmed the significant association between irrigation drainages and POPF (odds ratio 0.014, P = 0.01). Although not significant, mortality was lower in the irrigation group (4.2% vs 13.0%, P = 0.340). However, none of the fatalities in the irrigation-drainage group were POPF-related. No significant difference in length of hospital stay was observed between the 2 groups (18.0 vs 21.0 days, P = 0.091). Conclusions: Irrigation and drainage of the perianastomotic area represents a powerful approach to reduce POPF and, potentially, mortality after high-risk pancreaticoduodenectomies.